THE EFFECT OF BANKING FINANCIAL SOUNDNESS ON STOCK PRICES TO EARNINGS AND CAPITAL VARIABLES - Neli Hajar; Muhammad Tho'in; Musta'an Musta'an (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This research aims to determine the effect of banking soundness on stock prices as measured by several variables that are Earning and Capital. Earnings variables are ROA and NIM, while the Capital variable uses CAR. Banking that are the object of research are state-owned banks on the IDX 2011-2018. This research is quantitative descriptive. The independent variables of the research are ROA, NIM, and CAR, while the dependent variable is the stock price. The population in this study were 4 state-owned banks, namely BRI, BNI, BTN, and Mandiri Bank. The research sample is the assessment of the level of health with Earnings (ROA, NIM) and Capital (CAR) from financial reports published through http://www.idx.co.id. The data collection techniques using non-participant observation methods and financial reports. The data analysis technique used are descriptive statistical tests, classical assumption tests, while hypothesis testing was carried out by using multiple linear regression, t test, F test, and R2 test. The results showed that the Earning variable with ROA assessment and the Capital variable with CAR assessment had a positive and significant effect on stock prices, while the Earning variable with NIM assessment had a negative and significant effect on stock prices.